Stanford Type-A Aortic Dissection Masquerading as Acute Ischemic Stroke: A Case Report - Chao Liu; Jiangrong Ma; Bo Zhang; Ji Xie; Liyu Lu; Shinan Nie (Archives of Academic Emergency Medicine)
Aortic dissection (AD), a life-threatening cardiovascular emergency, is characterized by the separation of the aorta’s inner and middle layers due to a tear in the intima. It is classified as Stanford type A or B based on the tear’s location and extent. Symptoms vary but commonly include severe pain in the chest, back, or abdomen, along with atypical presentations such as shock, heart failure, or syncope. End-organ ischemia, including stroke and limb necrosis, may occur. Timely diagnosis and intervention are crucial for survival. Here, we report a 31-year-old male patient who presented with acute neurological symptoms, initially suspected of having a stroke, but was ultimately diagnosed with Stanford type A AD upon computed tomography (CT) angiography. This case underscores the importance of considering AD in the differential diagnosis of patients with neurological symptoms for accurate and prompt management.